Setting benchmark revision rates for total hip replacement: analysis of registry evidence. (9th March 2015) - Kandala, Ngianga-Bakwin; Connock, Martin; Pulikottil-Jacob, Ruth; Sutcliffe, Paul; Crowther, Michael J; Grove, Amy; Mistry, Hema; Clarke, Aileen
Abstract : Objective To compare 10 year revision rates for frequently used types of primary total hip replacement to inform setting of a new benchmark rate in England and Wales that will be of international relevance. Design Retrospective cohort study. Setting National Joint Registry. Participants 239 000 patient records. Main outcome measures Revision rates for five frequently used types of total hip replacement that differed according to bearing surface and fixation mode, encompassing 62% of all primary total hip replacements in the National Joint Registry for England and Wales. Revision rates were compared using Kaplan-Meier and competing risks analyses, and five and 10 year rates were estimated using well fitting parametric models. Results Estimated revision rates at 10 years were 4% or below for four of the five types of total hip replacement investigated. Rates differed little according to Kaplan-Meier or competing risks analysis, but differences between prosthesis types were more substantial. Cemented prostheses with ceramic-on-polyethylene bearing surfaces had the lowest revision rates (1.88-2.11% at 10 years depending on the method used), and cementless prostheses with ceramic-on-ceramic bearing surfaces had the highest revision rates (3.93-4.33%). Men were more likely to receive revision of total hip replacement than were women, and this difference was statistically significant for four of the five prosthesis types. Conclusions Ten year revision rate estimates were all less than 5%, and in some instances considerably less. The results suggest that the current revision rate benchmark should be at least halved from 10% to less than 5% at 10 years. This has implications for benchmarks internationally.